Optimal Energy Management in Coordination With Virtual Power Plant - Ranjan, Rishi Raj; Namrata, K.; Kumar, Ashish (IEEE International Students' Conference on Electrical, Electronics and Computer Science (Online), 2024)
The scarcity of fossil fuels such as coal, oil, and natural gas has increased the need for renewable energy sources (RESs) in recent years. Concerns about global warming are shared by many countries and industries in addition to the paucity of fossil resources. Due to these issues, modern distribution systems now include a large number of RESs. However, because renewable energy sources like photovoltaic (PV) and wind turbines are so widely used and are fluctuating, the power grid is subject to unpredictability and coordinated generation (WT). In this case, combining these resources offers a way to address problems brought about by their disparate results. The phrase "virtual power plant" describes a collection of connected Energy Storage Systems (ESSs), Distributed Generations (DGs), and controlled loads under the management of an EMS (VPP). The VPP's objective in this study is to lower total operating expenses while accounting for the cost of energy loss during a 24-hour period. In order to determine the optimal energy management for a case study combining a virtual power plant (VPP) with Renewable Energy Sources (RESs), Battery Storage Systems (BSS), and load control, an arithmetic optimization technique is proposed as a solution to the problem.